Learning about demand abroad from wholesalers: A B2B analysis - William Connell; Emmanuel Dhyne; Hylke Vandenbussche (National Bank of Belgium, 2019)
This paper uses Business to Business (B2B) transaction level data. It shows that manufacturing firms that initially export via a wholesaler are much more likely to become direct exporters to the same destination in subsequent periods. Theoretically, we rationalise this finding by demonstrating how a connection to a wholesaler reduces uncertainty about the foreign demand. In the data we isolate the channel for demand learning from productivity spillovers. Non-exporting manufacturing firms, previously serving a foreign destination through an exporting wholesaler, have a much higher probability of becoming direct exporters to the same export market in subsequent periods. A connection to an exporting wholesaler results in a probability of exporting to the same destination that is six times higher than a comparable firm without any exposure to the foreign destination.
Keywords: F14; L14; 330; wholesalers; indirect exports; learning